Electrically Switchable, Hyper‐Reflective Blue Phase Liquid Crystals Films. Issue 3 (18th December 2017) - Xu, Xiaowan; Liu, Zhen; Liu, Yanjun; Zhang, Xinhai; Zheng, Zhigang; Luo, Dan; Sun, Xiaowei
Abstract: Blue phase liquid crystals (BPLCs) with three‐dimensional periodicity have attracted significant attention due to their fast response time in the submillisecond region, which is critical in sequential liquid crystal displays and fast switchable photonic devices. However, the reflectivity of single‐layer BPLC films in the visible range, which is generally used for reflective display, is still low and limited to 50%, which hinders its use in a wide range of applications. Herein, hyper‐reflective, electrically switchable, fast responsive, and colorful reflective displays are demonstrated, which are based on multi‐layer BPLC films consisting of two single‐layer BPLC templates with opposite handedness. Hyper‐reflectivities of 89%, 82%, and 68% in the red, green, and blue color regions are achieved by refilling multi‐layer BPLC templates with achiral nematic liquid crystals. A reflectance switching of the film is achieved by unwinding the helical structure of the blue phase in an electric field, where the highest reflectance achieved in the red, green, and blue color regions is 94%, 86%, and 72%, respectively, in the presence of an electric field of 1 V µm −1 . Compared to previously demonstrated BPLC films, this newly developed multi‐layer BPLC film substantially improves the overall reflection efficiency by up to 3.6 times. Our study on hyper‐reflective BPLC film provides an attractive platform for future development including sequential colorful reflective displays and switchable optoelectronic devices. Abstract : Blue phase superstructure films with hyper‐reflectance in red, green, and blue are achieved, which provide an attractive platform for the future development of advanced displays, photonic and soft matter devices.